EFFECT OF CHICKEN MANURE BOKASI DIRT AGAINST GROWTH PLANT KALE (Ipomea Reptans) - Ramadhani Chaniag; Melani Yulanda.K (AGRIUM: Jurnal Ilmu Pertanian, 2016)
Applications of organic matter can improve soil structure, increase water holding capacity, and increase soil biological life. Chicken manure contains a complete nutrient required by plants for growth such as nitrogen (N), phosphorus (P) and potassium (K), calcium (Ca), magnesium (Mg) and sulfur (S). It is what lies behind our conduct research examining the effect of chicken manure fertilizer bokasi the kale plant (Ipomea reptans). This study was conducted in April-May 2016 New Mangkio village. The materials used in the experiment are: kale seed, soil, chicken manure, Gliricidia leaves, rice husks, EM4, sugar and water. The method in this study using a randomized block design (RAK). Comparison of land with bokasi consisting of 4 levels, namely: B0 = Without bokasi; B1 = Soil bokasi 2 kg + 0.5 kg; B2 = Soil bokasi 2 kg + 1 kg; B3 = Soil bokasi 2 kg + 1.5 kg. From observations we can conclude that: 1). Bokashi chicken manure contains organic C (14.47%); C / N ratio (17); pH H2O (7.51); N total (0.85%); Total P2O5 (0.98%); K2O total (2.57%). 2). B3 treatment effect on height, leaf length, number of leaves and stems of the plant kale circle.Keywords: Kale , Bokasi, Chicken manure.